Financial situation and political parties in local governments: Empirical evidence in the Spanish municipalities - Roberto Cabaleiro Casal; Enrique J. Buch Gómez; Antonio Vaamonde Liste (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
In contrast to several studies presented in the literature which analyze how different political elements affect specific aspects of financial management of public institutions, we have investigated from a comprehensive perspective how various political factors influence the financial situation of the municipalities. To do this, we use diverse multivariate techniques, the concept of financial condition and a large sample of Spanish municipalities. By isolating the electoral cycle and analyzing the essence of political factors, our main findings are that conservative and progressive parties do not present different behavior in relation to any of the financial dimensions. The territoriality of political parties influences the relationship between fund transfers received by the municipalities and certain expenses and investments. Furthermore, we did not detect that, in Spain, a partisan alignment exists between municipalities and the upper-level institutions.
Keywords: H70; 330; Local governments; Public finance; Public administration; Political parties